Oxford dictionary of phrase and fable - edited by Elizabeth Knowles (Oxford University Press, 2006)
Who or what is liable to jump the shark? Who first tried to nail jelly to the wall? Who was the first to cry "Women and children first"? The answers to these and many more questions are in this fascinating book. Here in one volume you can track down the stories behind the names and sayings you come across, whether in classic literature or today's news. Drawing on Oxford's unrivalled bank of reference and language online resources, this dictionary covers classical and other mythologies, history, religion, folk customs, superstitions, science and technology, philosophy, and popular culture. Extensive cross-referencing makes it easy to trace specific information, while every page points to further paths to explore. From "Barbie doll" to "bunny boiler," the dictionary gives reliable, up-to-date insights into the origin and history of words and phrases